A Novel Start-up Strategy for MMC-based Medium-voltage DC Distribution System with Low Inrush Current. Issue 1 (May 2021) - Yang, Limin; Zhu, Yiying; Lei, Ming
Abstract: To realize medium-voltage dc distribution system, the modular multilevel converter (MMC) is commonly adopted due to its high-level scalability and reliability for medium-voltage high-power energy conversion. Since the capacitors' voltages of the MMC are insufficient when the uncontrolled pre-charging stage is finished, large inrush current exists when the MMC is unlocked for active charging, which can cause malfunction of protection and threat the successful start-up of the whole system. This paper presents a detailed analysis on the causes of inrush current during the MMC's active charging process. Based on the analysis, a novel start-up strategy of the MMC is proposed to achieve improved controllability of the MMC's ac-side currents for inrush current suppression. The simulation results from a full-scale simulation model demonstrate that the inrush current can be effectively suppressed during the MMC's active charging process.